The Effect of Temperature and Solvent Concentration on Chemical and Physical Properties of Carrageenan from Gracilaria gracilis - Erawati, Emi; Fatoni, Rois; Hamid, Hamid; Noviasari, Tri (The Journal of Pure and Applied Chemistry Research, 2025)
Carrageenan is a polysaccharide extracted from seaweed sap using either air or an alkaline solution, such as Gracilaria gracilis. It functions as a thickening, emulsifying, suspending, and stabilizing agent. This paper reports the effect of KOH concentrations and temperatures on the extraction, in addition to determining the physical and chemical properties of the seaweed. A dried G. gracilis was soaked in distilled water for 24 hours and heated at 85°C for two hours. It was found the fat content was 3.56%, protein content 17.68%, moisture content 1.984%, and ash content of 26.547%. The highest values for water holding capacity (WHC) were 4.07 g/g, oil holding capacity (OHC) 3.539 g/g, swelling capacity (SC) at 1.894 mL/g, solubility index (SI) at 10.843 g/100g, emulsifying activity (EA) at 73.483%, and pH at 7.520.